SOCIAL BENEFITS IN STRUGGLE AGAINST POVERTY: SAMPLE OF GUMUSHANE - Mehmet Akif KARA (Fırat University, 2019)
The problem of poverty became more visible, especially after the 1990s, and became debatable in the "academic" summer. The debates on poverty and impoverishment are also related to the transformation of the state's economic policies. Along with the transition from social welfare state practices to "neoliberal" economic policies, "social policy" has also changed. Globalization and neoliberal policies have led to a gradual shrinking of social politics and a change of meaning. On the other hand, with the "social aid programs", the struggle against poverty has been tried to be continued. However, this "new process" brought with it debates such as impoverishing the poor and increasing social assistance addiction and charity culture. It is also argued that social policy will be reduced to social benefits through the discussions that are discussed in this study. After poverty, social policy and social assistance applications are theoretically addressed, social assistance and its types will be handled through the SYDV (Social Assistance and Solidarity Foundation) example operating in Gümüşhane Province within this theoretical-conceptual framework.